2017
DOI: 10.1097/md.0000000000008342
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen embolism caused by accidental subcutaneous injection of hydrogen peroxide during orthopedic surgery

Abstract: Introduction:We report a 39-year-old male patient with a fracture of the right acetabulum undergoing open reduction and internal fixation with a plate under general anesthesia. At closure, the surgeons injected 0.75% ropivacaine into the subcutaneous tissue of the incision wound for postoperative analgesia. Soon after injection, subcutaneous emphysema at the injection site and a sudden decrease in end-tidal CO2 tension with crude oscillatory ripples during the alveolar plateau phase were observed. Shortly ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…One study has even suggested that hydrogen peroxide actually contributes to aseptic loosening in the long-term; experimentally showing that the fatigue life of polymethyl methacrylate (PMMA) is reduced by a factor of 10, since hydrogen peroxide can affect the material properties of bone cement ( Guerin et al 2006 ). However, no subsequent research supporting this has been published, with various other studies in the literature proposing the opposite ( Chung and Jeong 2017 ).…”
Section: Uses Of Hydrogen Peroxide In Hip Arthroplastiesmentioning
confidence: 87%
“…One study has even suggested that hydrogen peroxide actually contributes to aseptic loosening in the long-term; experimentally showing that the fatigue life of polymethyl methacrylate (PMMA) is reduced by a factor of 10, since hydrogen peroxide can affect the material properties of bone cement ( Guerin et al 2006 ). However, no subsequent research supporting this has been published, with various other studies in the literature proposing the opposite ( Chung and Jeong 2017 ).…”
Section: Uses Of Hydrogen Peroxide In Hip Arthroplastiesmentioning
confidence: 87%
“…One major drawback of this treatment is that cumene hydroperoxide and/or hydrogen peroxide would be injected subcutaneously into the scalp, and neither peroxides have yet been characterized in any therapeutic capacity. However, a report from 2017 reported a case of oxygen embolism produced by accidental introduction of subcutaneous hydrogen peroxide ( 34 ). This suggests that caution should be taken if subcutaneous hydrogen peroxide injections were to be explored further as a modality of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…If this were to occur, serious complications could arise such as cardiac arrest [1], pulmonary embolism [2,3], and stroke [4].…”
Section: Introductionmentioning
confidence: 99%